The influence of behavioral finance on the decision of investors: empirical investigation from Pakistan Stock Exchange (Journal of Economic Research & Business Administration, 2020)
A high rate of return on the investment is crucially dependent on rational investment decision makingbecause rational investment decision ensures the successful return of an investment, especially instocks. Investment decision making is affected by many factors; most of them are related to psychologicaland behavioural. Since it is difficult to make rational decisions about investment, researchers are tryingto discover the factors that influence the investor’s behaviour about decision making. For the rationalestimation of success rate in stocks, investors have tried many traditional methods but reached on unsatisfactoryresults. However, Behavioral Finance has addressed this issue and discovered the most crucialfactors that may affect the investment decision making. Thus, this study aims to evaluate the influenceof the factors of behavioural finance that affect decision making in the stock exchange. Three factorshave been selected and used to gauge the impact on investment decision making. These factors include;overconfidence bias, representativeness bias, and availability bias. A structured close-ended questionnairehas been used to collect the data, and data was collected from 211 respondents who are investorson Karachi stock exchange. To analyze the collected data, multiple linear regression (MLR) model hasbeen used. The result of this study shows that all three independent variables have a significant impacton investment decision making. Moreover, the relationship is positive between the independent anddependent variables. Therefore, it can be concluded that the null hypothesis is rejected. This study willassist investors to make decisions rationally in the stock market.